Contraction Principles in Metric Space - Jha, Pavan Kumar (NUTA Journal, 2024)
This paper deals with contractions in metric. some historical accounts on contractions principles in metric space. Banach Contraction Principle is marvelous and widely applied fixed point theorem in nonlinear analysis. every contraction in a complete metric space has a unique fixed point.